RESPON BURSA SAHAM TERHADAP STRATEGI DIVERSIFIKASI PENDAPATAN PERBANKAN - Rafif, Helmi; Bustaman, Yosman (Emerging Markets : Business and Management Studies Journal, 2020)
We evaluate how the Indonesian stock market has reacted to the banking diversification revenue strategy in the period of 2009-2016. The market reactions are measured by the ratio of market equity capitalization to its book value equity (MB) and market viability or solvency is proxied by the bank?s market-based Z score. Using panel data regression, we find that the higher the level of diversification of bank revenue response positively by the market indicating by improving on banks? capitalization ratio and market solvency. It shows that revenue diversification could produce a significant impact on bank profitability and reduce the probability of bank failure. Additionally, our results reveal that the larger size of the bank, the riskier the bank, however,these larger banks could achieve higher market equity capitalization that protects them from insolvency problems. Banks having large book equity capital response positively by the market, it indicates a positive relationship between this variable and Z score.